2004
DOI: 10.1111/j.1475-3588.2004.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Multisystemic Treatment of Antisocial Adolescents in Norway: Replication of Clinical Outcomes Outside of the US

Abstract: Background: MST is an intensive home-and community-based intervention for youths with serious antisocial behaviour and other serious clinical problems, which has been effective at reducing out-of-home placements and producing favourable long-term clinical outcomes in the US. The aims of the study were to determine the degree to which these outcomes would be replicated in Norway for youths with serious behaviour problems and to conduct a randomised trial of MST by an independent team of investigators. Method: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
1
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(146 citation statements)
references
References 29 publications
8
123
1
13
Order By: Relevance
“…This program expansion facilitated the conduct of RCTs outside the United States. Completed randomized trials in Norway (Ogden & Halliday-Boykins, 2004) and Canada (Leschied & Cunningham, 2002) generally show that at posttreatment, youth randomized to MST demonstrated a greater decrease in both internalizing and externalizing behavior problems, self-reported criminal activity, self-reported antisocial beliefs and attitudes, and frequency and length of stays in out-of-home placements than youth receiving usual services. Long-term outcomes from Norway indicated that at 2 years postintake, youth who received MST continued to demonstrate significantly reduced time in out-of-home placement, parent report of internalizing problems, youth report of delinquency, and teacher report of both internalizing and externalizing behavior problems compared to youth in the control group (Ogden & Hagen, 2006).…”
Section: Mst Research Outcomesmentioning
confidence: 99%
“…This program expansion facilitated the conduct of RCTs outside the United States. Completed randomized trials in Norway (Ogden & Halliday-Boykins, 2004) and Canada (Leschied & Cunningham, 2002) generally show that at posttreatment, youth randomized to MST demonstrated a greater decrease in both internalizing and externalizing behavior problems, self-reported criminal activity, self-reported antisocial beliefs and attitudes, and frequency and length of stays in out-of-home placements than youth receiving usual services. Long-term outcomes from Norway indicated that at 2 years postintake, youth who received MST continued to demonstrate significantly reduced time in out-of-home placement, parent report of internalizing problems, youth report of delinquency, and teacher report of both internalizing and externalizing behavior problems compared to youth in the control group (Ogden & Hagen, 2006).…”
Section: Mst Research Outcomesmentioning
confidence: 99%
“…MST workers operate within a team structure and have small caseloads; they are available to their clients 24 hours a day, 7 days a week (Littell, 2005). MST is often used (and has been successful) with recidivist youth offenders and this treatment involves strengthening family relationships, communication, and processes (Ogden & Halliday-Boykins, 2004). Strengthening family relationships is an important issue across a variety of social issues including mental health (Clark, 2001;Falloon, 2003); and the maltreatment of children (Sar, Antle, Beldsoe, Barbee & Can Zyl, 2010) which, if not treated, can lead to mental health issues and antisocial/ criminal behaviour (Bender, 2010).…”
Section: Relating the Findings Of The Research To Criminal Behaviourmentioning
confidence: 99%
“…Ogden and Halliday-Boykins 2004;Huey et al 2000;Borduin et al 1995). Recently conducted meta-analyses of the effectiveness of MST (Curtis et al 2004), including 11 studies and 708 participants, showed a moderate effect size (d= 0.50) on indicators of criminal activity.…”
Section: Research Into the Effectiveness Of Mstmentioning
confidence: 99%
“…A recently published review by Littell (2005) has questioned the conclusion that MST is effective by pointing out that inconsistent and incomplete reports have been published, which sometimes contained unclear randomization procedures and inadequate analyses. Also, with a few exceptions (Leschied and Cunningham 2002;Ogden and Halliday-Boykins 2004;Timmons-Mitchell et al 2006), most of the empirical support, including the meta-analysis by Curtis et al (2004), comes from the studies conducted by the same group of researchers who also developed and implemented MST. A meta-analysis conducted by Littell et al (2005) showed much less promising results.…”
Section: Research Into the Effectiveness Of Mstmentioning
confidence: 99%